Who is blameworthy? social identity and intergroup bullying - Gini, Gianluca ([California] Sage Publication, 2006)
Using social identity theory (SIT; Tajfel and Turner, 1979) and social identity development theory (SIDT; Nesdale, 1999) as a framework, this study investigated attitudes towards inter-group bullying at school. Preadolescent boys and girls (n = 314) participated in a study, utilizing the short story technique, in which they were induced to identify with their own school-class, whose social status was manipulated to be high or low. A story was told in which the group engaged in an episode of physical bullying as either the bully group or the victim group. The designed out-group was another class of the same school. Attribution of blame to both the in-group and the out-group was assessed. Results showed a higher preference for the in-group when it was the victimized group. Moreover, participants blamed the high status out-group more than any other group. The results are discussed in relation to the literature about bullying and the application of SIT and SIDT to this domain.
Includes bibliographical references.
Keywords: Bullying; Intergroup relations